Measuring Religious Moderation Among Muslim Students at Public Colleges in Kalimantan Facing Disruption Era - Nuraliah Ali (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2020)
This study aimed to describe the religious moderation of students at public colleges in Kalimantan on the basis of four indicators of moderation. The type of this study was a qualitative-quantitative descriptive research using concurrent embedded research model. The result of this study showed that the understanding, response, and religious method of students had a characteristic, namely moderate value. The level of moderate indicator in each aspect was higher than the indicator that was not moderate, or extreme. In the aspect of knowledge, students were not familiar enough with the tag line “religious moderation”, and the provision of the religious moderation material in the form of socialization or a forum of scientific discussion was still limited. In aspect of behavior, students showed tolerance, national commitment, rejecting violence, and accommodating local culture. In the aspect of the religious method, the students who were categorized as moderate in facing religious problems preferred to uphold moral values, character, and identity of Islam rahmatan lil alamin rather than use violence in solving problems. Facing the disruption era, most students could filter information they obtained and know how to process information they received wisely and responsibly, confirm and consider the truth first, and know the advantage of information before distributing it to many people.